Activities of Information and RAN Library Council and the participation in it the representatives of the Siberian science - B. S. Elepov; E. D. Dyachenko; L. P. Pavlova (Библиосфера, 2011)
2011 is the year of the 100th anniversary of the foundation of ILC RAS. The history of its formation and development is rich on events and particular deeds. It played a great role in creating the system of informationlibrary service in Russian science and particularly in Siberian one. The article discloses the history of ILC in the context of development of libraries within the Siberian Branch of RAS.